2015
DOI: 10.2147/ndt.s82328
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude, and practice related to epilepsy: a community-based study

Abstract: Religious and sociocultural beliefs influence the nature of treatment and care received by people with epilepsy. Many communities in Africa and other developing nations believe that epilepsy results from evil spirits, and thus, treatment should be through the use of herbaceous plants from traditional doctors and religious leadership. Community-based cross-sectional study designs were used to assess the knowledge, attitude, and practice related to epilepsy and its associated factors by using a pretested, semi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
38
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 22 publications
11
38
2
1
Order By: Relevance
“…In contrast to our findings, a community-based study in Ethiopia revealed that knowing someone with epilepsy is positively associated with the level of knowledge and practices related to epilepsy [20]. We also found that the KBP score was influenced by sex and females had slightly higher KBP scores than males.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, a community-based study in Ethiopia revealed that knowing someone with epilepsy is positively associated with the level of knowledge and practices related to epilepsy [20]. We also found that the KBP score was influenced by sex and females had slightly higher KBP scores than males.…”
Section: Discussioncontrasting
confidence: 99%
“…[7] It was reported that 44.8% of their respondents indicated their refusal to marry people with epilepsy. [41] This is in consistent with the findings of this research report. Further discussion indicated that nearly 35% of the students believed that persons with epilepsy could not lead a happy married life.…”
Section: Attitude Towards Epilepsysupporting
confidence: 93%
“…[34] Similar findings by various authors showed that respondents equate epilepsy to mental illness. [39,40,41,42] It is obvious from the discussions on this issue of suspicion of mental illness that majority of the nurses for this study associate epilepsy with mental illness and this points to lack of knowledge of the disease.…”
Section: Attitude Towards Epilepsymentioning
confidence: 97%
“…In Africa, epileptics who have neurological, physical, and psychiatric morbidities do not get adequate care leading to increase in mortality and morbidity 131415. In many African communities, the lack of qualified medical personnel also means that people living with epilepsy who have neurological, physical, and psychiatric comorbidities never get adequate care leading to increased morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Improving public knowledge about epilepsy has been shown to influence positively on the attitudes of the public toward sufferers in Africa 1112131415. Various studies in Nigeria have assessed the awareness of epilepsy among various groups and communities,1112131415 but none to the knowledge of the authors has looked at traders in the Mid-West region of Nigeria. This study aims to document the knowledge of childhood epilepsy by community members using traders (market women and men in a popular market in Benin City, Nigeria) as a case study.…”
Section: Introductionmentioning
confidence: 99%